Penerapan Media Pembelajaran Genially untuk Meningkatkan Hasil Belajar IPA di SD Muhammadiyah - Nailah Fatma; Ichsan (Genderang Asa: Journal of Primary Education, 2022)
The purpose of this study is to determine the application of genially learning media to improve science learning outcomes for students of SD Muhammadiyah Condongcatur. The method used is quantitative form one group pretest-posttest design. The subjects in this study were 20 students in class IVB of SD Muhammadiyah Condongcatur. The data collection technique uses multi-limb multiple choice test questions consisting of 20 questions. The data were analyzed using the Paired Sample T-Test test, from the results of the t test obtained a significance value (2- tailed) from the pretest and posttest was 0.000 < 0.05, then Ha was accepted, meaning that there was an increase in science learning outcomes with the application of genially media, so it can be concluded that genial-based learning media can improve the learning outcomes of grade IVB students at SD Muhammadiyah Condongcatur keyword;Genially media, Science